Meningkatkan Aktivitas Belajar dan Hasil Belajar Siswa dengan Penerapan Model Pembelajaran Mind Mapping - Novrika Rusyiana; Rofiq Irmawan (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2015)
On the tenth grade students of APK 3 at SMKN 2 Kediri, it is known that they have low achievement. The research finding showed that the Mind Mapping learning model is able to make students to be active and creative as well as helping students to improve their learning activities and outcomes Office Administration subject. This can be seen based on the value of learning activities that is observed by 3 observers. The average value of student activity before the given action was only 72.8 with criterion B (good). Furthermore, the average value of the class in the first cycle after the implementation of Mind Mapping learning model increased to be 75.8 with B (good) criterion. In the second cycle, the average value increased student learning activities to be 82 with criterion B (good). Meanwhile, the learning outcome of students is also increased during the study. The average value of daily tests before given action is 75 the number of students who completed a total is 18 students, while the average value of the first post-test cycle is 82.4 with a number of students who passed is as many as 23 students and the average value of post test cycle II is 91.1 with a number of students who completed as many as 34 students.Abstrak: Di kelas X APK 3 SMKN 2 Kediri diketahui bahwa nilai aktivitas belajar dan hasil belajar siswa rendah. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran Mind Mapping mampu menjadikan siswa aktif dan kreatif serta membantu siswa untuk meningkatkan aktivitas belajar dan hasil belajar mereka pada mata pelajaran Administrasi Perkantoran. Hal tersebut terbukti pada nilai aktivitas belajar yang diamati oleh 3 orang observer. Nilai rata-rata aktivitas belajar siswa sebelum diberi tindakan hanya 72,8 dengan kriteria B (baik) Selanjutnya nilai rata-rata kelas pada siklus I setelah adanya penerapan model pembelajaran Mind Mapping meningkat menjadi 75,8 dengan kriteria B (baik). Pada siklus II nilai rata-rata aktivitas belajar siswa meningkat menjadi 82 dengan kriteria B (baik). Sedangkan hasil belajar siswa juga mengalami peningkatan selama penelitian. Nilai rata-rata ulangan harian sebelum diberi tindakan adalah 75 dengan jumlah siswa yang tuntas sebanyak 18 orang siswa sedangkan nilai rata-rata post test siklus I adalah 82,4 dengan jumlah siswa yang tuntas sebanyak 23 orang siswa dan nilai rata-rata post test siklus II adalah 91,1 dengan jumlah siswa yang tuntas sebanyak 34 orang siswa.